Genome-wide analysis of the TIFY family in Lycium and the negative regulation of stomatal development by LrJAZ2 gene - Zhao, Jiqing (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2023 Elsevier Masson SAS. All rights reserved.